2012
DOI: 10.1093/humrep/des030
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced paternal obesity in the absence of diabetes diminishes the reproductive health of two subsequent generations of mice

Abstract: This is the first observation of paternal transmission of diminished reproductive health to future generations and could have significant implications for the transgenerational amplification of subfertility observed worldwide in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
180
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(214 citation statements)
references
References 38 publications
22
180
1
3
Order By: Relevance
“…62 While fathers cannot provide direct nourishment to the young after birth, additional attention should be paid to whether a healthy diet of the father, and the mother, before conception can lead to long-term beneficial offspring consequences. It is increasingly becoming apparent that sub-optimal paternal diets, those high in fat or protein restricted, can result in negative offspring sequelae, [14][15][16][17][18][19][20][21][146][147][148][149] but the impacts of a healthy diet have been largely ignored. In conclusion, much work remains on identifying various steps that both parents can adapt to ensure the lifelong health of their offspring and potentially even triumph over negative influences that the conceptus or neonate may encounter.…”
Section: Discussionmentioning
confidence: 99%
“…62 While fathers cannot provide direct nourishment to the young after birth, additional attention should be paid to whether a healthy diet of the father, and the mother, before conception can lead to long-term beneficial offspring consequences. It is increasingly becoming apparent that sub-optimal paternal diets, those high in fat or protein restricted, can result in negative offspring sequelae, [14][15][16][17][18][19][20][21][146][147][148][149] but the impacts of a healthy diet have been largely ignored. In conclusion, much work remains on identifying various steps that both parents can adapt to ensure the lifelong health of their offspring and potentially even triumph over negative influences that the conceptus or neonate may encounter.…”
Section: Discussionmentioning
confidence: 99%
“…This was evident as a reduction in meiotic progression, increased oocyte arrest and altered mitochondrial function at 17 weeks of age, despite the offspring being fed a CD [16]. When mated to normal weight males, these females also give birth to F2 offspring who themselves have impaired metabolic and reproductive function [15,16].…”
Section: Tod Fullston and Helana Shehadeh Contributed Equally To Thismentioning
confidence: 99%
“…The perturbed reproductive health of female offspring sired by obese fathers was initially characterized by impaired oocyte maturation and impaired mitochondrial function at 17 weeks of age [16]. But the ability of these offspring to produce developmentally competent embryos and quality of their resultant embryos are not known for a much earlier age that predates any metabolic disturbances (i.e., 5 weeks of age).…”
Section: Tod Fullston and Helana Shehadeh Contributed Equally To Thismentioning
confidence: 99%
“…24,25 A number of studies have reported that a parental diet containing high fat or imposing calorie restriction modulates the phenotype of the offspring. [26][27][28] Under-nourishment in utero leads to methylome changes in the sperm of the male progeny and metabolic changes that are inherited to the subsequent generation. 29 A high fat paternal diet in rodents changes the insulin and glucose levels in offspring serum and induces an abnormal response after glucose or insulin injections.…”
Section: Introductionmentioning
confidence: 99%